2019
DOI: 10.4103/ijpsym.ijpsym_355_19
|View full text |Cite
|
Sign up to set email alerts
|

Comments on “Correlation of Cognitive Resilience, Cognitive Flexibility and Impulsivity in Attempted Suicide”

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms. How to cite this article: Verma T. Comments on "Correlation of cognitive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…We excluded studies ( n = 6) that exclusively focused on SIIs in the context of autistic spectrum disorders and/or intellectual developmental disorders, as the function of SII in these clinical groups may often differ from those endorsed more broadly (Summers et al, 2017). We also excluded one study that otherwise met our inclusion criteria due to errors in reported statistical analyses and its potential influence on the authors’ interpretation of results (see Verma, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…We excluded studies ( n = 6) that exclusively focused on SIIs in the context of autistic spectrum disorders and/or intellectual developmental disorders, as the function of SII in these clinical groups may often differ from those endorsed more broadly (Summers et al, 2017). We also excluded one study that otherwise met our inclusion criteria due to errors in reported statistical analyses and its potential influence on the authors’ interpretation of results (see Verma, 2019).…”
Section: Methodsmentioning
confidence: 99%